Two-Dimensional Numerical Modelling of Interaction of Micro-Shock Wave Generated by Nanosecond Plasma Actuators and Transonic Flow - M. Abdollahzadeh (2014)
The influence of nanosecond pulse-driven, surface-mounted dielectric barrier discharge(DBD) actuators on a transonic flow is studied numerically. An airfoil representing turbomachinery blades in transonic flow is considered as a test case. A two-dimensional fluidmodel of DBD is used to describe the plasma dynamics. The model couples fluid dischargeequations with compressible Navier-Stokes equations. Simulations were conducted withan airfoil of NACA 3506 profile in a transonic condition of M = 0.75. When a nanosecondpulse voltage is used, with a rise and a decay time of the order of nanoseconds, a significant amount of energy is transferred in a short time from the plasma to the fluid, whichleads to the formation of micro-shock waves and therefore to the modification of flow features. Moreover, a plasma energy deposition model is developed and presented by usingthe results of the plasma discharge model.